LISTRIK DAN PENGARUHNYA TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI MALUKU - Sapthu, Andre (Jurnal Cita Ekonomika, 2023)
Electricity has a very important role in influencing a country's economic growth. High electricity consumption is often an important indicator of the level of industrialization and technological progress in an economy. In this research, we will examine theoretically the influence of electricity consumption and labor variables on economic growth. To analyze the relationship between variables in the research model, we use a regression equation model using annual data. The research results show that the electricity consumption variable significantly influences economic growth, while labor does not significantly influence economic growth and has a unidirectional relationship. Increased productivity supported by a reliable electricity supply can increase efficiency in the production of goods and services, trigger growth in the industrial sector, and create jobs. Strong electricity consumption also encourages investment in energy infrastructure that can stimulate economic growth.